Anti-Inflammatory Effects of Huberia peruviana Cogn. Methanol Extract by Inhibiting Src Activity in the NF-κB Pathway - Seung A Kim (MDPI AG, 2021)
There is a growing need to develop anti-inflammatory drugs to regulate inflammatory responses. An extract of Huberia peruviana Cogn. had the best inhibitory effect on nitric oxide (NO) production in screening process undertaken in our laboratory. However, the anti-inflammatory effect of Huberia peruviana Cogn. methanol extract (Hp-ME) has not been studied. In this study, the anti-inflammatory effect of Hp-ME was assessed by using an NO assay, RT-PCR, luciferase reporter gene activity assay, western blotting assay, HCl/EtOH-induced acute gastritis model, and LPS-induced acute lung injury model. The phytochemical components of Hp-ME were determined through LC-MS/MS analysis. When RAW264.7 and HEK293T cells were treated with Hp-ME, NO production was decreased dose-dependently without cytotoxicity and the mRNA levels of iNOS, COX-2, and TNF-α were decreased. In a luciferase assay, the activity of transcription factors, NF-κB in TRIF or MyD88-overexpressing HEK293T cells was extremely reduced by Hp-ME. The western blotting analysis indicated that Hp-ME has anti-inflammatory effects by inhibiting the phosphorylation of Src. Hp-ME showed anti-inflammatory effects on in vivo models of HCl/EtOH-induced gastritis and LPS-induced acute lung injury. LC-MS/MS revealed that Hp-ME contains several anti-inflammatory flavonoids. The final findings of this study imply that Hp-ME could be used as an anti-inflammatory drug in several inflammatory diseases.